2022
DOI: 10.31557/apjcp.2022.23.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Association between VDR Gene Polymorphisms and Melanoma Susceptibility in a Colombian Population

Abstract: Mutations and polymorphisms in the vitamin D receptor gene (VDR) were highly correlated with melanoma and other types of cancer. VDR is a transcription factor that regulates the expression of several genes through

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Since the discovery of VDR polymorphism a number of papers have been published studying VDR gene and the position of different SNPs and their role in various diseases (Table 1 , Fig. 3 ) [ 15 , 34 41 ].…”
Section: Vitamin D Receptor Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of VDR polymorphism a number of papers have been published studying VDR gene and the position of different SNPs and their role in various diseases (Table 1 , Fig. 3 ) [ 15 , 34 41 ].…”
Section: Vitamin D Receptor Polymorphismsmentioning
confidence: 99%
“… Caccamo et al [ 40 ] 2020 Italy Case control Fok I, Bsm I GH Significant association was found between Fok I and Bsm I with GH. Aristizabal-Pachon et al [ 41 ] 2022 Colombia Case control Fok I, Taq I Melanoma cancer Fok I polymorphism was associated with melonma cancer risk. Taq I polymorphism was associated with a protective effect against this cancer.…”
Section: Vitamin D Receptor Polymorphismsmentioning
confidence: 99%